DEKOMPOSISI TUGAS-TUGAS SOFTWARE-DEFINED RADIO (SDR) - Marpanaji, Eko (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
This paper addresses decomposition of the tasks of Software-Defined Radio (SDR) computation by taking Gaussian Minimum Shift Keying (GMSK) as a case study. The aim of this research was to produce a task graph of the SDR that was needed in scheduling of distributed computing with task parallelism using genetics algorithm. Based on the tasks decomposition and the evaluation of execution time of each task, we obtained a task graph of SDR computation. We conclude that there are eleven tasks for the modulator and fifteen for the demodulator.